Kajian Teologis Terhadap Ketidaktaatan Adam dan Ketaatan Kristus dalam Teologi Paulus - Putra, Adi; Namang, Kezya Thresia; Nome, Nehemia; Keluanan, Yane Henderina (Jurnal Kala Nea, 2022)
This research examines theologically the expressions of Adam and Christ in Paul's theological perspective. This is quite interesting to study, and the purpose of this research is to clarify Paul's intention when he felt this way in his letter. Researchers used qualitative methods, especially literature or literature review in this study. First, the theological emphasis of the expressions of Adam and Christ is to state about Adam's disobedience and vice versa Christ's obedience. Second, the emergence of the phrases Adam and Christ in Paul's letters will create a significant and striking difference between the first Adam who brought sin to the world and the second Adam, namely Christ who brought life to the world. Third, this phrase also wants to emphasize how well the quality of the second Adam is much higher and nobler than the quality of the first Adam. That is why, everyone who has been born again in the second Adam (namely Christ) will experience eternal life with the true source of life.